Telangcator 2.0 - a natural acid-base indicator from butterfly pea flower / Ummi Kalthum Mansor and Asniati Sabil - Mansor, Ummi Kalthum; Sabil, Asniati (Universiti Teknologi MARA, Kedah, 2023)
Telang or Butterfly pea flower (Clitoria ternatae) is abundantly found in Malaysia. Its petals have vibrant violet-blue colour; hence it is most commonly used as food colouring. Telangcator is an innovation that is able to become an alternative acid-base indicator from Telang flowers. Extract of Telang flowers is prepared from maceration of dried Telang flowers. The extract is used to produce two (2) types of acid-base indicators; natural Telangcator pH paper and natural Telangcator pH liquid indicator. For Telangcator pH paper, Whatman filter paper was soaked in the Telang extract for 10 minutes and left to dry at room temperature. The dried filter paper was cut into 10 mm wide strips and used as pH papers. For Telangcator pH liquid indicator, the leftover Telang extract was used directly as pH liquid indicator. When tested on various household substances to determine their reliability as acid-base indicators, both the Telangcator pH paper and the Telangcator liquid indicator changed colour from violet-blue to red in acidic substances and violet-blue to green in basic substances. When conducted with Kolej Matrikulasi Negeri Sembilan (KMNS) students, the Telangcator activity has been successful in gaining their interests in pursuing Science subjects at university. Furthermore, the activity has been found to be interesting to the public when displayed and demonstrated during Open Day KMNS. Both the natural Telangcator pH paper and Telangcator liquid pH indicator are suitable to be used as alternative acid-base indicators in schools and other education institutions as their productions are cost-effective and not harmful to the environment.